LA ENSEÑANZA DE ‘COLOCACIONES’ EN ESPAÑOL COMO L2: UNA PROPUESTA DIDÁCTICA - Álvarez Cavanillas, José Luis; Chacón Beltrán, Rubén (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Lexical collocations are groups of two or more words that come up together on a regular basis. In non-native language teaching, in general, and in the teaching of Spanish as an L2, in particular, it seems necessary to pay attention to this linguistic feature from a pedagogical point of view. Failure in the production of appropriate lexical collocations does not usually lead L2 learners to a communication breakdown, but students tend to produce unnecessary circumlocutions when trying to convey their messages. This study provides an overall perspective to the analysis of lexical collocations, takes up previous research on the topic and makes use of mental maps as a convenient teaching technique. Some teaching materials were designed and used with a group of students of Spanish as an L2. In this paper we report the effects of this empirical intervention and draw some pedagogical implications for the teaching of lexical collocations in Spanish as an L2.